Diabetes mellitus and oral mucosa alterations: Prevalence and risk factors - Bastos, Alliny de Souza [UNESP]; Perin Leite, Andressa Rosa [UNESP]; Spin-Neto, Rubens [UNESP]; Nassar, Patricia Oehlmeyer; Massucato, Elaine Maria Sgavioli [UNESP]; Orrico, Silvana Regina Perez [UNESP] (Elsevier B.V., 2011)
Aims: To investigate the prevalence of oral mucosa alterations in patients with type 2 diabetes and to identify possible risk factors related to oral mucosa alterations.Methods: 146 patients with type 2 diabetes and 111 age-and gender-matched healthy controls subjects were consecutively recruited from Araraquara School of Dentistry to answer a structured questionnaire designed to collect demographic data as well as current and former history of diabetes. Clinical examination of the oral mucosa was carried out by a stomatologist.Results: A higher prevalence of oral mucosa alterations was found in patients with diabetes than in patients without diabetes (p < 0.001), with significant difference to development conditions (p < 0.0001), potentially malignant disorders (p < 0.0001) and fungal infections (p < 0.05). In the multiple logistic regression, diabetes (odds ratio 9.9 IC 5.11-19.16) and smoking habit (odds ratio 3.17 IC 1.42-7.12) increased the odds of oral mucosa alterations significantly.Conclusions: Patients with diabetes mellitus not only showed an increased prevalence of oral mucosa alterations but also a significant percentage of potentially malignant disorders. These findings elucidate the necessity of regular clinical examination to ensure early diagnosis and prompt management of oral mucosa lesions in patients with diabetes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Diabetes mellitus; Diagnosis; Prevalence; Mucosa; Oral pathology